From the modeling of diadromous species’ marine distributions to the characterization of their current and future marine habitats - Navarro, Clara; Janc, Anais; Lassalle, Géraldine; Lambert, Patrick; Dambrine, Chloé (Frontiers in Marine Science, 2023)
Introduction Many diadromous fish species are currently facing the threat of generalized population extirpations across their range, and conservation efforts implemented primarily within the continental domain may not be sufficient to ensure their viability. In consequence, better understanding the use of the marine environment by these species turned out to be critical. Material and method We developed marine species distribution models for two species, Allis shad (Alosa alosa) and the European flounder (Platichthys flesus), and proposed a way to interpret the habitat suitability from a more functional perspective. Our approach defined marine habitats as highly suitable environments that remained with a high potential through the species life stage duration at sea. First, a species-specific probabilistic threshold was applied to select for highly suitable environments each year of the simulations. Then, annual maps of high suitability were combined into recurrence maps showing areas were the environmental conditions remained the most suitable across the life at sea of the given species, these areas being called ‘marine habitats’. We applied this approach to study the current and future marine habitats of Allis shad and European flounder under climate change scenarios. Results The main current marine habitats of these species were coastal, primarily in the Bay of Biscay for Allis shad and in the English Channel-North Sea for European flounder. These habitats are expected to experience minimal changes by mid-century, and the species may even benefit from new habitats at higher latitudes. However, the European flounder is likely to face greater challenges in the central part of its range by the end of the century, as potential spawning grounds may be threatened. Discussion This study provided a way to rethink ‘traditional’ suitability maps by integrating basic knowledge on the diadromous species life at sea. Our findings were part of a larger effort to link continental and marine habitats in improving management of diadromous species.